Kan fibrations which are homomorphisms of simplicial groups (1973)
In [3] C. Ruiz  gave a definition for "fibration" on the category Annb of Banach rings which is closely related to a functorGR : Annb→△ Gr which takes its values on the category of the simplicial groups. It was assumed that the fibration / of Annb  are the Banach ring homomorphisms such that the homomorphisms   GR(f) of simplicial groups, are Kan fibrations. This notion happened to be equivalent (Cf. [3; p. 169]) to the notion of Serre fibration given by KAROUBI and  VILLAMAYOR [4].